Tribological properties of palm oil bio-lubricant with modified carbon nanotubes - Hamimi Abdul Razak, Izatul; Ali Ahmad, Mohamad; Nurul Nabihah Ahmad Fuad, Nadia; Syazwani Shahrudin, Khairul; ., . (International Journal of Engineering and Technology, 2018)
Vegetable oil has been identified to be the one of best replacement of mineral oil. Palm oil has also been used as replacement for current mineral oil apart from the application in domestic use. Its potential as based oil for hydraulic fluid, diesel engine, and lubricants has been confirmed in many previous studies. Additives are commonly added to lubricant oils with purpose to enhance the oil performance. Recent studies show that the size and quantity of additives used may play a big role in its tribological properties. Several studies reported that adding nanoparticles with the size between 1 to 100 nm into lubricating oil at certain weight percentage can reduce friction and improve anti-wear properties. Modification of lubricant oil with nanoparticle capable to give the sliding effect into rolling effect thus reduces surface contact and heat production. In the present work, carbon nanotube has been used as the Nano-additives in palm oil bio-lubricant. Four-ball tester was used to investigate its tribological properties under boundary lubrication (metal to metal contact). Result obtained shows that the addition of 0.04 wt% of carbon nanotubes recorded the lowest coefficient of friction with a 10.8% improvement compared to the pure palm oil. The additive also contributed to better wear scar diameters and possessed good anti wear properties for palm oil. This thus shows the significant potential of the carbon nanotubes as the wear preventive additive for palm oil bio-lubricant.Â Â